2014
DOI: 10.3390/molecules20010135
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Affinity Profiling of Neuroactive Polyphenols for Post-Traumatic Calpain Inactivation: A Molecular Docking and Atomistic Simulation Sensitivity Analysis

Abstract: Calcium-activated nonlysosomal neutral proteases, calpains, are believed to be early mediators of neuronal damage associated with neuron death and axonal degeneration after traumatic neural injuries. In this study, a library of biologically active small molecular weight calpain inhibitors was used for model validation and inhibition site recognition. Subsequently, two natural neuroactive polyphenols, curcumin and quercetin, were tested for their sensitivity and activity towards calpain's proteolytic sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The results were presented as an analytico‐mathematical representation of potential energy surfaces with total energy composed of bond stretching, angle, and torsional contributions as bonding and van der Waals interactions, H‐bonding and electrostatic functions as nonbonding energies. The reactional profiles for component molecules and their complexes were elucidated by exploring the spatial disposition of the various component molecular attributes . This review report provides an outlook of various molecular modeling templates generated to date and provides a brief account of rationale and results obtained from these in silico studies.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results were presented as an analytico‐mathematical representation of potential energy surfaces with total energy composed of bond stretching, angle, and torsional contributions as bonding and van der Waals interactions, H‐bonding and electrostatic functions as nonbonding energies. The reactional profiles for component molecules and their complexes were elucidated by exploring the spatial disposition of the various component molecular attributes . This review report provides an outlook of various molecular modeling templates generated to date and provides a brief account of rationale and results obtained from these in silico studies.…”
Section: Introductionsupporting
confidence: 71%
“…The reactional profiles for component molecules and their complexes were elucidated by exploring the spatial disposition of the various component molecular attributes. 2 This review report provides an outlook of various molecular modeling templates generated to date and provides a brief account of rationale and results obtained from these in silico studies. The details of the in silico methods employed in the studies are out of scope of this review and can be extracted from the individual references provided within the subsections.…”
Section: Introductionmentioning
confidence: 99%
“…Though van der Waals interactions are weaker than covalent and electrostatic bonding but this bond in large is responsible for free energy change and made the major contribution to the total binding energies (Sood et al 2018;Mohanty et al 2018;Keretsu et al 2019). These interactions are known to stabilize the binding interface structures through intermolecular energy minimization (Kumar et al 2015;Arthur and Uzairu 2019). In this study we observed a large number of van der Waals interactions stabilizing the FtsZ and interacted small molecule docking complex.…”
Section: Discussionmentioning
confidence: 57%
“…MDL28170 is a cell permeable selective peptidomimetic inhibitor of calpain 1 and 2 that binds to the protease enzymatic site and inhibits its action. 22,23 IM-12 is a novel cell permeable indolyl maleimide which inhibits GSK-3β by competing for ATP binding. 24 The MDL28170 and IM-12 powder was dissolved in dimethyl sulfoxide (DMSO) and administered to the pigs orally.…”
Section: Methodsmentioning
confidence: 99%